Long-term evolution of estimated glomerular filtration rate in patients with type 2 diabetes and heart failure. (14th October 2021) - Escabia, C; Codina Verdaguer, P; Buchaca, D; Spitaleri, G; Domingo, M; Santiago-Vacas, E; Cediel, G; Zamora, E; Alonso, N; Troya, M.I; Santesmases, J; Crespo, E; et al.
Abstract: Background: Limited data are available on the very long-term trajectory of glomerular filtration rate (GFR) in patients with chronic heart failure (HF) and type 2 diabetes mellitus (T2D). Purpose: To prospectively assess dynamic trajectories of GFR estimated by CKD-EPI in a real-life cohort of HF patients based on the presence or absence of T2D over a 14-year follow-up. Methods: In a prospective observational registry of real-life HF outpatients, estimated GFR (eGFR) was calculated by CKD-EPI at baseline and on a structured schedule every 3 months up to 14 years. We included in the analysis only eGFR values that were assessed at scheduled visits, discarding urgent renal function assessments. Loess (locally weighted error sum of squares) curves were plotted for the subgroups according to baseline T2D up to 14 years of follow-up. Loess curves are useful to observe a trend or relationship on nonlinear data observed over time. Results: 2386 patients were consecutively included from August 2001 to December 2018. 43.2% of the patients had a history of T2D. Mean age was 67.0±12.6 years, 28.9% were women and 71.0% had HF with reduced ejection fraction (EF<40%). 25080 eGFR values were included in the analysis with a median of 8 values per patient [IQR 4–15] and a range between 1 and 47. Diabetic patients had a worse baseline eGFR and presented a persistent decline over time. On the contrary non-diabetic patients presented an early decrease, mid-term improvement and a late progressive decline (Figure 1). Conclusions: eGFR long-term trajectories in diabetic and non-diabetic patients with chronic HF were significantly different. Funding Acknowledgement: Type of funding sources: None.